2021
DOI: 10.1002/cam4.4100
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories and risk factors for anxiety and depression in children and adolescents with cancer: A 1‐year follow‐up

Abstract: BACKGROUND There is limited data on the longitudinal trajectories of psychiatric disorders in children with cancer and risk factors for their persistence. The current study aimed to longitudinally assess the trajectories and risk factors for anxiety and depressive symptoms and disorders in children and adolescents with cancer. METHODS Children and adolescents with cancer and their parents completed the Patient‐Reported Outcomes Measurement Information System (PROMIS) Depression and Anxiety Module and were inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Similarly, the cutoff point for probable depression was set at T≥59.9, equivalent to the PHQ-9 standard cutoff score for moderate depression (=10) ( Bevans et al, 2014 ; Choi et al, 2014 ). PROMIS was validated in Hebrew using the standard procedure of translation and back translation by independent bilingual English-Hebrew speakers ( Yardeni et al, 2021 , 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, the cutoff point for probable depression was set at T≥59.9, equivalent to the PHQ-9 standard cutoff score for moderate depression (=10) ( Bevans et al, 2014 ; Choi et al, 2014 ). PROMIS was validated in Hebrew using the standard procedure of translation and back translation by independent bilingual English-Hebrew speakers ( Yardeni et al, 2021 , 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The majority of the articles analyzed found that children and adolescents with cancer experienced anxiety and depression. According to Yardeni et al (2021), 48% of children experienced anxiety and/or depression at least once throughout the follow-up period. This is similar to Eldin et al, (2019), who found that cancer children had more mood swings, anxiety disorders, panic attacks, and separation anxiety than the control group (p = 0.001).…”
Section: Negative Psychological Changesmentioning
confidence: 99%
“…Currently, there are no clear indications approved by the Food and Drug Administration (FDA) [ 28 ] or European Medicines Agency (EMA) [ 29 ] for psychopharmacological medications in medically ill children with delirium, depression, or anxiety [ 30 , 31 , 32 , 33 ].…”
Section: Clinical Questionsmentioning
confidence: 99%